Development of Integrated Science Learning Modules Integrated with Local Wisdom to Improve Science Literacy - Sulviana; Afadil Sukarman; Muslimin; Amiruddin Kade; Achmad Ramadhan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an integrated science learning module that integrates local wisdom from the megalithic sites in the Bada Valley to improve science literacy and critical thinking skills among students at Al-Khairaat 2 Palu Junior High School. The main problems are low science literacy among students and minimal utilization of local potential in science learning. The method used was Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data were collected through expert validation, practicality questionnaires, and effectiveness tests with a sample of students and school teachers. Analysis was conducted based on the validity, practicality, and effectiveness of the module using Cohen's d to measure the improvement in students' skills. The validation results showed that the module was valid and practical to use, with a high effectiveness score (0.87). The use of the module significantly improved students' science literacy in the indicators of explaining scientific phenomena, evaluating scientific investigations, and interpreting data, with average scores of 89%, 76%, and 60%. In conclusion, this local wisdom-based science learning module is effective in improving the quality of science learning, science literacy, and students' critical thinking skills, as well as strengthening their character and concern for the surrounding culture and environment.